Bringing the state back in the lithium triangle: An institutional analysis of resource nationalism in Chile, Argentina, and Bolivia - Johnson, Craig A. (2024)
International efforts to tackle climate change have ignited a global surge in demand for the “critical metals” that are used in the production of lithium-ion batteries and electric vehicles (EVs). Among them, lithium represents a critical strategic component that is concentrated in only a limited number of extractive zones. In theory, limited availability and strong demand creates favourable conditions for producer states. In practice, many states have struggled to nationalize the production of battery-grade lithium, reflecting the dominant role that multinational corporations play in the sector. This paper explores the strategies that producer states in Chile, Argentina, and Bolivia have used to navigate this rapidly changing dynamic, making the case that the recent surge in demand for battery metals has created new opportunities for challenging the oligopoly of multinational capital but the ability of governments to reorient production linkages for enhancing incomes, technical capacity, and economic opportunity in the production of lithium derivatives remains structurally and historically constrained by the institutional legacies of nationalization and social mobilization that vary across the three states. Drawing upon the “political settlements” literature, we contend that national and subnational efforts to exert greater control over the lithium sector can be attributed to the institutional legacy of political contestation and the role of social actors in crafting new power configurations that challenge dominant state-business coalitions.